CIDADES-ESPAÇOS IN-VISÍVEIS: ESTRANGEIRANDO-SE POR ESPAÇOS DE DIMENSÕES FORMATIVAS NA CIDADE - Fonseca, Danuza de Oliveira (2021)
This thesis seeks to discuss about the formative power of experiences arising from walking around the city, especially Vitória Downtown, since we believe in its formative dimensions. We bet on the device of walking, of circularity, as experiments that trigger in us processes of training that goes beyond unschooled spaces and that lets us touch in encounters with other bodies, spaces, knowledge, in an attempt to unveil cracks, shakes, (un) constructions that are often not considered, or barely visible in the city. The thesis is that training, via some spaces, streets, alleys inhabited in the city, are important vectors of experimentation in the training processes, which are engendered through the possibilities of encounters, weaving a rhizomatic network across the city. Alongside the school spaces, it is proposed to make loci visible in the city to think about formative movements, which are made through a connection with a great diversity of actors who produce paths, which provide opportunities for meetings, which unfold in movements of re- existence. The work is based on the method of cartography, as it is believed that this methodological direction is more in tune with the research objectives and in relation to its main theoretical lines. The idea was to dig in into these threads and warps running through spaces in the Center of the city as rich formative granaries of new ethos, without losing sight of the fact that power and resistance do not dissociate. As a support, the verb “to foreigner” was created as a way to better explainour moves both in writing and in field trips.